INFLUENCE OF MOTIVATION ON PERFORMANCE EMPLOYEES AT Global Intermedia Nusantara - Fatimah, Siti; Lastari, SE.,MM, Siwi (Management, 2010)
This study intends to investigate the influence of motivation on employee performance PT. Global Intermedia Nusantara Yogyakarta. Data collection methods used were interviews and questionnaires. While the methods of data analysis used descriptive and quantitative analysis of the measurement method can be expressed by the numbers. Based on the analysis of multiple regression equation with t test (individual test) showed that payroll, affect employees´ performance with t calculate equal to 2.845 is greater than 2.0117 or t table (2.845> 2.0117). The work environment affects job performance with t calculate equal to 2.475 is greater than 2.0117 or t table (2.475> 2.0117). While career development affect work performance of 2.141 is greater than 2.0117 or t table (2.141> 2.0117). F test results (Test unison) showed that payroll, work environment, career development jointly affect employees´ performance with the F test of 14.988 is greater than F table 3.19. (14.988> 3.19). While the variable remuneration, is the most dominant variable affecting job performance, it is based on the resulting beta coefficient (.345) is greater than the coefficient of work environment (0.305) and development work (0.250). Employees´ performance is affected by payroll, work environment, career development by 46.1%, while the remaining amount of 53.9% is influenced by factors not investigated. Key words: influence. work performance, employees